STUDI FENOMENOLOGI: KEBUTUHAN PENINGKATAN KOMPETENSI PERAWAT AMBULANS DALAM PELAYANAN DI PREHOSPITAL KALIMANTAN TIMUR - Misbah Nur Jannah* Retty Ratnawati** Ali Haedar*** (The Indonesian Journal of Health Science, 2016)
Prehospital system is a services that given out of hospital in emergencysituation. Ambulan’s Nurse in giving services ussually have psychologic problemarise from himself. The problem that come from nurse very influence the nurse actin making decicions. This study was qualitative interpretif involving 6 ambulan’snurse. Data gathered from deep interview and analyzed with Braun and Clarcktechnic. Ambulan’s nurse having problem with emergency decicion’s making.Problem that arise from herself because they think that they not capable to doanything. Uselessness arise because nurse feel not confident and worried for theircapability. This feeling actually influence the decicions making that should be donequickly. Ambulance nurse experience in giving prehospital services very influencedby capability and experienced they had before. Incresing nurse competency isimportant factor to increasing prehospital services. Nurse competency can beincreased by on going education and training. Ambulans nurse that directly involveon emergency case can increase they experience’s.